Epistolary Becomings: Archival Traces and Diffractive Readings - Tamboukou, Maria (Tautosakos darbai, 2025)
In this paper, I offer the concept of diffraction as both a methodological approach and an epistemological lens. This dual move has guided my archival research, encompassing various types of archival documents, and has shaped my reading, understanding, and analysis of letters by European women mathematicians, who lived and worked in the eighteenth and nineteenth centuries. The discussion draws on a Leverhulme-funded research project of writing a feminist genealogy of automathographies, tracing the process of becoming a woman mathematician, philosopher, and scientist. I argue that analogue, digitised, and photographed letters should be regarded as distinct types of archival documents, each positioning the researcher in unique, but entangled ways relative to their sources and data. Furthermore, recognizing the interweaving of personal and scientific elements in the correspondence of women mathematicians is crucial for understanding the formation of the female self in the realms of gender, science, and mathematics.